Assessing Public Housing Residents' Awareness on maintenance management towards sustainable Housing:the case of Penang. - Yusof, Nor' Aini (Universiti Sains Malaysia, 2013)
The study seeks to investigate the effectiveness of maintenance management by the public housing building managers and residents. Effective maintenance management is conceptualized to constitute knowledge on maintenance, response method and maintenance priority preference. A survey was conducted with the residents of multi-storey public housing in Penang, Malaysia, who were selected using random sampling. A descriptive analysis, Pearson product-moment correlation, and multiple regression analysis were used to analyse the data. Kajian ini bertujuan menyelidiki keberkesanan pengurusan penyenggaraan oleh pengurus bangunan dan penghuni perumahan awam. Pengurusan penyenggaraan yang berkesan mengandungi 3 konsep iaitu penetahuan tentang penyenggaraan,kaedah tindakbalas dan keutamaan penyenggaraan.Satu kajian telah dijalankan dengan penduduk perumahan awam berbilang tingkat di Pulau Pinang, Malaysia, yang dipilih secara rawak. Satu analisis deskriptif, Pearson produk-saat korelasi dan analisis regresi berganda telah digunakan untuk menganalisis data.